The influence of stents on microbial colonization of the airway in children after slide tracheoplasty: A 14‐year single‐center experience. Issue 1 (20th March 2014) - Rijnberg, Friso M.; Butler, Colin R.; Speggiorin, Simone; Fierens, Anja; Wallis, Colin; Nouraei, Reza; McLaren, Clare A.; Roebuck, Derek J.; Hewitt, Richard; Elliott, Martin J.
Summary Objectives This study describes the microbial colonization profile of the airway in children after slide tracheoplasty (STP) with and without stents, and compares colonization to children undergoing cardiothoracic surgical procedures without airway related disease. Methods A 14‐year retrospective single case note review was performed on patients undergoing STP and stent insertion. Nose and throat (NT) and bronchoalveolar lavage (BAL) specimens were analyzed for microbial profile and expressed as cumulative mean microorganisms per patient (MMP). Results Forty‐three patients (median age ± SD 15.02 ± 31.76 months) underwent STP and 141 patients underwent cardiothoracic but no airway surgery (median age ± SD 31.7 ± 47.2 months). Sixteen patients required a stent after STP. One‐hundred seventy‐two positive microbial specimens were identified. The predominant 6 microorganisms were (1) Staphylococcus aureus; (2) Pseudomonas aeruginosa; (3) Haemophilus influenzae not type B; (4) Coliforms; (5) Streptococcus pneumoniae; and (6) Candida Albicans, and accounted for 128 (74%) of all positive specimens found. Children with stents had more MMP compared to children without stents after STP [4.06 ± 2.38 and 2.04 ± 2.24 MMP (P < 0.001), respectively]. Both groups of children after STP had more MMP compared to the control group (P < 0.001). Children with stents had more microbial colonization of their lower respiratory tract compared to their upper respiratory tract (3.36 ± 2.02 and 1.36 ± 0.93 MMP (P < 0.01) respectively). Staphylococcus aureus colonization of the lower respiratory tract was significantly higher in children with stents compared to children without stents after STP [0.5 and 0.15 MMP (P < 0.05) respectively]. Conclusions This study indicates airway surgery and the subsequent use of stents to be a significant risk factor for microbial colonization of the airway in children. More specifically airway stents appear to increase colonization in the distal airway, which appears unrelated to that of the upper respiratory tract. Pediatr Pulmonol. 2015; 50:79–84.Pediatr Pulmonol. 2015; 50:???–???. © 2014 Wiley Periodicals, Inc.